Contextual Factors, Health History, and Daily Living Activities for Ovarian Cancer Risks: A Case-Control Study in Indonesia - Restuning Widiasih; Windy Natasha; Tosin Popoola; Katherine Nelson (Nurse Media: Journal of Nursing, 2023)
Background: Women are encouraged to aware for risk factors that may aid in the early detection of ovarian cancer before symptoms and sign appear. However, limited studies evaluated the broad aspects of the risk factors for ovarian cancer, particularly in Indonesia. For a more thorough analysis of ovarian cancer risk factors, more variables and a research approach that can make it easier to uncover risk factors of ovarian cancer are necessary. Detecting factors associated with ovarian cancer could serve as the foundation for developing an early warning model.